(3OhQ EJaGbjI JMQjQ JLGQI GdNOeGJ GdOhdjI (B((3GdLGJS(B) (3aj QaY caGAI COGA GdNOeGJ GdeUQajIs - (3SGej CMeO eMeO(B, (3eQGOs ((3GdbGgQI(B:s (3GdecJH GdYQHj ddeYGQa,s, 2005)
(3jVe GdGWGQ GdYGe ddOQGSI, fTCI GdLGJ hJWhQgG heHGOFgG, GdNOeGJ GdeUQajI hGdJRGeGJ eUQ aj GJaGbjI GdLGJSs
(3HjHdjhZQGajG(B: (3U(B.309s
Keywords: (3GdHfhcs; (3GdHfhc(B- (3GdMSGHGJ GdeUQajI s; (3eUQ(B- (3GdHfhc s